2017
DOI: 10.1111/jcmm.13396
|View full text |Cite
|
Sign up to set email alerts
|

Effect of human amniotic epithelial cells on pro‐fibrogenic resident hepatic cells in a rat model of liver fibrosis

Abstract: Myofibroblasts are key fibrogenic cells responsible for excessive extracellular matrix synthesis characterizing the fibrotic lesion. In liver fibrosis, myofibroblasts derive either from activation of hepatic stellate cells (HSC) and portal fibroblasts (PF), or from the activation of fibroblasts that originate from ductular epithelial cells undergoing epithelial-mesenchymal transition. Ductular cells can also indirectly promote myofibroblast generation by activating TGF-b, the main fibrogenic growth factor, thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…Amniotic Epithelial Cells (AEC), a subset of placental stem cells, can be addressed to experience EMT for redirecting their biological fate [6][7][8][9] . Indeed, AEC have been proved capable to interact with different typologies of host damaged tissue such as lung 10 , liver 11 , cholangiocyte 12 , CNS 13 , tendon 14 or sinusoidal endothelial cells 11 by promoting regeneration, managing inflammation and replacing damaged cells with functional/mature ones (without cell fusion). The level of maturation implies either a tissue replacement as epithelial cells [15][16][17][18][19][20][21] , or as mesenchymal cells by experiencing 1 Faculty of Bioscience and Technology for Food, Agriculture and Environment, University of Teramo, Teramo, Italy.…”
Section: Epithelial-mesenchymal Transition (Emt) Is a Complex Biologimentioning
confidence: 99%
See 1 more Smart Citation
“…Amniotic Epithelial Cells (AEC), a subset of placental stem cells, can be addressed to experience EMT for redirecting their biological fate [6][7][8][9] . Indeed, AEC have been proved capable to interact with different typologies of host damaged tissue such as lung 10 , liver 11 , cholangiocyte 12 , CNS 13 , tendon 14 or sinusoidal endothelial cells 11 by promoting regeneration, managing inflammation and replacing damaged cells with functional/mature ones (without cell fusion). The level of maturation implies either a tissue replacement as epithelial cells [15][16][17][18][19][20][21] , or as mesenchymal cells by experiencing 1 Faculty of Bioscience and Technology for Food, Agriculture and Environment, University of Teramo, Teramo, Italy.…”
Section: Epithelial-mesenchymal Transition (Emt) Is a Complex Biologimentioning
confidence: 99%
“…During AEC in vitro expansion, EMT is avoided by adopting specific cultural protocols 11,26 in order to preserve their native key functional attitude such as stemness, plasticity and immunomodulatory activity 26,27 . In particular, the mesenchymal transition of AEC can be controlled by progesterone (P 4 ) that exerted a powerful inhibitor role by interfering with the TGF-β1 signaling pathways.…”
mentioning
confidence: 99%
“…These preclinical studies successfully demonstrated the significant therapeutic properties of hAEC as a candidate stem cell for regenerative medicine. Promising data from in vitro studies that have demonstrated the immunomodulatory properties of hAECs and have prompted a number of preclinical studies using models for lung fibrosis, liver fibrosis, wound healing, arthritis, colitis, multiple sclerosis, graft‐vs‐host disease and brain injury . Decellularized amniotic membrane has also been utilized clinically in the field of ophthalmology as a scaffold for corneal restoration.…”
Section: Therapeutic Potential Of Amniotic Epithelial Cellsmentioning
confidence: 99%
“…Several reports have shown that transplantation of human MSCs of different origins (e.g., umbilical cord [6,65,66], amniotic mesoderm [67,68], bone marrow [9,[69][70][71], liver [72], etc. ), without prior hepatic commitment can support liver function and/or alleviate symptoms of liver failure in both animal models as well as human patients [73][74][75].…”
Section: Undifferentiated Mesenchymal Stromal Cellsmentioning
confidence: 99%